Stringbean : the life and murder of a country music legend - Hagood, Taylor, 1975- (Music in American life., 2023)
"A beloved member of the country music community, David "Stringbean" Akeman found nationwide fame as a cast member of Hee Haw. The 1973 murder of Stringbean and his wife forever changed Nashville's sense of itself. Millions of others mourned not only the slain couple but the passing of the way of life that country music had long represented. Taylor Hagood merges the story of Stringbean's life with an account of murder and courtroom drama. Mentored by Uncle Dave Macon and Bill Monroe, Stringbean was a bridge to country's early days. His instrumental savvy and old-time singing style drew upon a deep love for traditional country music that, along with his humor and humanity, won him the reverence of younger artists and made his violent death all the more shocking. Hagood delves into the unexpected questions and uneasy resolutions raised by the atmosphere of retribution surrounding the murder trial and recounts the redemption story that followed decades later"--